Oxidative addition of (bromoethynyl) benzene to κ 2-acetylacetonatobis (trimethylphosphine) rhodium (I) - Marie-Hélèn, Thibault; Meng Guan, Tay; Andrei S, Batsanov; Judith AK, Howard; Todd B, Marder (Elsevier, 2013)
The reaction of (bromoethynyl)benzene with κ2-acetylacetonatobis(trimethylphosphine)rhodium(I), [Rh(acac)(PMe3)2] 1, was followed by in situ1H and 31P NMR spectroscopy. The kinetic product is that of cis-oxidative addition of the C–Br bond to Rh, and this species rearranges to the thermodynamically more stable trans-oxidative addition product trans-[Rh(acac)(Br)(CCPh)(PMe3)2] 3. The structures of both 1 and 3 have been determined by single-crystal X-ray diffraction.